Pelaksanaan Kegiatan Ekstrakurikuler Musikalisasi Puisi di SMA Negeri 1 Kota Lubuklinggau - Yuventio Dwi Arampan; Harisnal Hadi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to describe "The Implementation of Poetry Musicalization Extracurricular Activities at SMA Negeri 1 Lubuklinggau City". This type of research is qualitative descriptive. Data collection techniques by means of observation, interviews, literature studies and documentation. Data analysis techniques by means of data collection, data reduction, data presentation, and conclusion making. The results of the research on "Implementation of Extracurricular Activities for Poetry Musicalization at SMA Negeri 1 Lubuklinggau City". The design of poetry musicalization extracurricular activities is to design rehearsal activities for 1 time a week and are carried out with 5 meetings. The activities carried out by the students were exercises in the formation of grubs and working on poetry into poetry musicals. The extracurricular achievement of poetry musicalization is to be able to work on poetry into a work of poetry musicalization, master the theme and meaning implied in each verse of the poem, and participate in poetry musicalization festival events at the high school level in South Sumatra.